Comparison of Public College Librarians' Performance, Competence, and Work Design in Indonesia and Malaysia - Mutia, Fitri; Soesantri, Tri; Prasetyo, Helmy; Atmi, Ragil Tri; Hamzah, Mohd. Faizal; Masrek, Mohamad Noorman (Program Studi Ilmu Perpustakaan UIN Alauddin, 2024)
Public college libraries are crucial in developing a nation's human resources. This study compares academic librarians' performance, competence, and work design in Indonesia and Malaysia. Utilizing purposive sampling, the study included 380 academic librarians from both countries. The findings indicated no significant difference in the performance of college librarians between Indonesia and Malaysia. Similarly, no significant difference was found in the competency levels of librarians in the two countries. Regarding work design, no difference was observed in task characteristics, as indicated by a p-value above 0.05. However, significant differences were identified in the knowledge characteristics of work design, with a p-value below 0.05. A significant difference was confirmed by t-test analysis, where the t-value (4.944) exceeded the critical value (1.960) at α = 0.05. These results highlight similarities and distinctions in the professional roles and capabilities of academic librarians in Indonesia and Malaysia, offering insights for potential improvements in library management and human resource development in these regions.